Molecular epidemiology of dengue in Malaysia: 2015–2021 - Chem, Yu Kie; Yenamandra, Surya Pavan; Chong, Chee Keong; Mudin, Rose Nani; Wan, Ming Keong; Tajudin, Norazimah; Abu Bakar, Rehan Shuhada; Yamin, Mohd Asri; Yahya, Rokiah; Chang, Chia-Chen; Koo, Carmen; Ng, Lee Ching; et al. (Frontiers in Genetics, 2024)
Dengue has been one of the major public health problems in Malaysia for decades. Over 600,000 dengue cases and 1,200 associated fatalities have been reported in Malaysia from 2015 to 2021, which was 100% increase from the cumulative total of dengue cases reported during the preceding 07-year period from 2008 to 2014. However, studies that describe the molecular epidemiology of dengue in Malaysia in recent years are limited. In the present study, we describe the genetic composition and dispersal patterns of Dengue virus (DENV) by using 4,004 complete envelope gene sequences of all four serotypes (DENV-1=1,567, DENV-2=1,417, DENV-3=762 and DENV-4=258) collected across Malaysia from 2015 to 2021. The findings revealed that DENV populations in Malaysia were highly diverse, and the overall heterogeneity was maintained through repetitive turnover of genotypes. Phylogeography analyses suggested that DENV dispersal occurred through an extensive network, mainly among countries in South and East Asian and differentMalaysian states, as well as among different states, especially within Peninsular Malaysia. The results further suggested Selangor and Johor as major hubs of DENV emergence and spread in Malaysia.